Jan Karłowicz w świetle materiałów archiwalnych : dialektologia, etnolingwistyka i lituanistyka - Rak, Maciej (Wydawnictwo Księgarnia Akademicka, 2021)
JAN KARŁOWICZ IN THE LIGHT OF ARCHIVAL MATERIALS: DIALECTOLOGY, ETHNOLINGUISTICS AND THE STUDY OF LITHUANIAN LANGUAGE AND CULTURE The book refers to the scientific activity of Jan Karłowicz, and, in particular, to the three areas to which he contributed much of his work: dialectology, ethnolin- guistics, and the study of Lithuanian Language and Culture. The material basis includes the researcher’s archival works (files of the Lexicon of Polish Dialects [Słownik gwar polskich], Lexicon of Polish Mythology [Słownik mitologii polskiej] and the Little Lexicon of Lithuanian Mythology [Słowniczek mitologii litewskiej]), found in 2017 in the Scientific Archive of PAN and PAU in Kraków. The objective of this book is to publish these documents and re-analyse the Lexicon of Polish Dialects. For more than a hundred years, i. e. since the time in which the lexicon was finished in 1911, nobody has probably read those manuscripts. One of the reasons for this is the fact that they were catalogued in a wrong manner